HABILIDADES SOCIAIS NA ESCOLHA PROFISSIONAL: UMA PROPOSTA DE INTERVENÇÃO PARA ADOLESCENTES - VASCONCELOS, MARIA HELENA VENÂNCIO DE (2021)
Adolescence is a period of change in all aspects of peoples lives. The search for a profession is part of this period, which is surrounded by doubts, biopsychosocial transformations, by the intense reflection on studies and a professional future. In this sense, it is understood the importance of an elaborated repertoire of Social Skills to contribute to the process of professional choice. Therefore, the objective of this work is to propose a Social Skills Program protocol of professional choice for the context of adolescence. For this, two studies were carried out. In Study 1, an analysis of national and international articles is carried out on intervention protocols for skills aimed at professional choice. In Study 2, the objective is to present a SSP protocol of professional choice for the context of adolescence. The project's effectiveness is expected in the future, thus collaborating in the professional choice process through the SS.